Impact of Federalism on Women’s Empowerment in Nepal: Case of Chandragiri Municipality - Pandey, Baikuntha (THE ACADEMIA, 2025)
Women's empowerment in Nepal has been a soaring issue since the promulgation of the Federal Republic Constitution in 2015. The foundation of women's empowerment ensures women's economic participation, educational attainment, and political representation. The challenges include disparities in access to resources and services, cultural norms that shape gender roles, and the effectiveness of local initiatives promoting gender equality. Understanding these factors is essential for fostering inclusive development and empowering women within the community. This study aimed to evaluate the state of women's empowerment after the introduction of federalism and analyze the impact of local government actions on women's empowerment in the area. The research used a descriptive design, focusing on Kathmandu's Chandragiri Municipality, Ward 12. A random sample of 121 households from the municipality provided data on women's empowerment. The data was analyzed using descriptive statistical tools such as frequency tables, percentages, and t-tests. The findings indicated that the local government positively affected various aspects of women's empowerment, including property ownership rights, decision-making in family budgets, investment and expenditure, recreational choices, and responsibilities related to child health and education. The study concluded that public policies promoting the participation of women have significantly influenced socio-economic aspects both within families and the broader society. It is recommended to support efforts aimed at developing policies and programs that promote women's empowerment and to assist local governments, policymakers, and agencies in implementing these initiatives in Chandragiri Municipality.